A Supramolecular Antidote to Macromolecular Toxins Prepared through Coassembly of Macrocyclic Amphiphiles. Issue 40 (21st August 2021) - Pan, Yu‐Chen; Yue, Yu‐Xin; Hu, Xin‐Yue; Li, Hua‐Bin; Guo, Dong‐Sheng
Abstract: Poisoning is a leading cause of admission to medical emergency departments and intensive care units. Supramolecular detoxification, which involves injecting supramolecular receptors that bind with toxins to suppress their biological activity, is an emerging strategy for poisoning treatment; it has few requirements and a broad application scope. However, it is still a formidable challenge to design supramolecular therapeutic materials as an antidote to macromolecular toxins, because the large size, flexible conformation, and presence of multiple and diverse binding sites of biomacromolecules hinder their recognition. Herein, a supramolecular antidote to macromolecular toxins is developed through the coassembly of macrocyclic amphiphiles, relying on heteromultivalent recognition between the coassembled components and toxic macromolecules. The coassembly of amphiphilic cyclodextrin and calixarene strongly and selectively captures melittin, a toxin studied herein; this imparts various therapeutic effects such as inhibiting the interactions of melittin with cell membranes, alleviating melittin cytotoxicity and hemolytic toxicity, reducing the mortality rate of melittin‐poisoned mice, and mitigating damage to major organs. The use of the proposed antidote overcomes the limitation of supramolecular detoxification applicability to only small‐molecular toxins. The antidote can also detoxify other macromolecular toxins as long as selective and strong binding is achieved because of the coassembling tunability. Abstract : Supramolecular detoxification is an emerging strategy for treating poisoning; however, developing supramolecular therapeutic materials as an antidote to macromolecular toxins is challenging. To overcome this challenge, a heteromultivalent coassembling material (CCA‐CD) comprising macrocyclic amphiphiles is developed. The CCA‐CD binds with melittin strongly and selectively, and significantly alleviates its toxicity, serving as a novel supramolecular antidote used for melittin poisoning treatment.